Current Understanding of the Pathogenesis of ANCA-Associated Vasculitis and Novel Treatment Options Targeting Complement Activation - Konstantinos Drouzas; Petros Kalogeropoulos; George Liapis; Sophia Lionaki (Life)
Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (ANCA-vasculitis) is an autoimmune disease characterized by inflammation and necrosis of small or medium vessels. In the past, the role of the complement in the pathogenesis of ANCA-vasculitis has been underestimated, due to the paucity of the complement at sites of injured glomeruli. Following evidence from animal models of the major role of the complement in pathogenesis of ANCA-vasculitis, the complement has again attracted interest. Immunohistology analysis of pauci-immune glomerulonephritis—ANCA glomerulonephritis (ANCA-GN)—reveals the presence of complement products and membrane attack complex, suggesting their involvement in the disease process. Researchers emphasize the complement classical or lectin pathway as a contributor to the development of ANCA-vasculitis. The era of targeted therapies to suspend the complement activation as a therapy for ANCA-vasculitis has arrived, and thus, the comprehension of its role is very important. This review summarizes recent insights on the important role of complement activation in the development of ANCA-vasculitis as well as the emerging therapeutic possibilities that target complement components for the treatment of this condition.